2004
DOI: 10.1002/lt.20145
|View full text |Cite
|
Sign up to set email alerts
|

Use of fenoldopam to control renal dysfunction early after liver transplantation

Abstract: With the aim of assessing whether fenoldopam can help to preserve renal function after liver transplantation, we randomized 140 consecutive recipients with comparable preoperative renal function to receive fenoldopam 0.1 g/kg/ minute (group F, 46 patients), dopamine 3 g/kg/minute (group D, 48 patients), or placebo (group P, 46 patients) from the time of anesthesia induction to 96 hours postoperatively. There were no differences between the groups in intraoperative urinary output or furosemide administration (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
(51 reference statements)
0
22
0
1
Order By: Relevance
“…A very recent study reported a beneficial effect of fenoldopam in liver transplant recipients after 72 hrs of infusion (20). Therefore, the 4-day infusion was considered sufficient to give both drugs a chance to produce an appreciable clinical effect.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A very recent study reported a beneficial effect of fenoldopam in liver transplant recipients after 72 hrs of infusion (20). Therefore, the 4-day infusion was considered sufficient to give both drugs a chance to produce an appreciable clinical effect.…”
Section: Discussionmentioning
confidence: 97%
“…Fenoldopam seems to exert a renoprotective effect when administered prophylactically in patients undergoing elective aortic surgery (16,17) or cardiopulmonary bypass (18). Moreover, fenoldopam seems to preserve renal function by counterbalancing the renal vasoconstrictive effects of cyclosporine in kidney (19) and liver (20) transplant patients. The effects of fenoldopam administration in patients at high risk of radiographic contrast nephropathy are controversial.…”
mentioning
confidence: 97%
“…1,2,[8][9][10][11] Various strategies have been investigated to minimize the risk of acute renal failure after orthotopic liver transplantation, such as optimization of hemodynamic conditions in the operative and perioperative periods, but these strategies have not been successful. [12][13][14][15] Delaying the initiation of the nephrotoxic CNIs cyclosporine and tacrolimus until renal function recovers appears to be a logical approach to minimize early renal dysfunction in liver transplantation. Results from recent clinical studies have demonstrated the safety and efficacy of this strategy; [16][17][18][19][20][21] however, there is concern that delaying the initiation of CNI may place patients at risk for early acute rejection.…”
mentioning
confidence: 99%
“…Our results are in accordance with only two previous reports in which fenoldopam was used at a low dosage (9) or for a short period of time. (10) All the other studies (7,8,(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Discussionmentioning
confidence: 99%